Hydrogen Sulfide Releasing Capacity of Natural Isothiocyanates: Is It a Reliable Explanation for the Multiple Biological Effects of Brassicaceae? - Citi, Valentina; Martelli, Alma; Testai, Lara; Marino, Alice; Breschi, Maria C.; Calderone, Vincenzo (Planta Medica, 2014)
Hydrogen sulfide is an endogenous pleiotropic gasotransmitter, which mediates important physiological effects in the human body. Accordingly, an impaired production of endogenous hydrogen sulfide contributes to the pathogenesis of important disorders. To date, exogenous compounds, acting as hydrogen sulfide-releasing agents, are viewed as promising pharmacotherapeutic agents. In a recent report, the hydrogen sulfide-releasing properties of some synthetic aryl isothiocyanate derivatives have been reported, indicating that the isothiocyanate function can be viewed as a suitable slow hydrogen sulfide-releasing moiety, endowed with the pharmacological potential typical of this gasotransmitter. Many isothiocyanate derivatives (deriving from a myrosinase-mediated transformation of glucosinolates) are well-known secondary metabolites of plants belonging to the family Brassicaceae, a large botanical family comprising many edible species. The phytotherapeutic and nutraceutic usefulness of Brassicaceae in the prevention of important human diseases, such as cancer, neurodegenerative processes and cardiovascular diseases has been widely discussed in the scientific literature. Although these effects have been largely attributed to isothiocyanates, the exact mechanism of action is still unknown. In this experimental work, we aimed to investigate the possible hydrogen sulfide-releasing capacity of some important natural isothiocyanates, studying it in vitro by amperometric detection. Some of the tested natural isothiocyanates exhibited significant hydrogen sulfide release, leading us to hypothesize that hydrogen sulfide may be, at least in part, a relevant player accounting for several biological effects of Brassicaceae.
Keywords: hydrogen sulfide; H2S-donors; Brassicaceae; natural isothiocyanates; glucosinolates